SYARIAH BASED ECONOMIC DEVELOPMENT - Muhammad Irsyad (Proceeding International Seminar of Islamic Studies, 2023)
The sharia economic system can be an alternative to the conventional banking system because this system has a fairly strong resistance to the current global financial crisis. Opportunities in the development of Islamic economic research arose along with the emergence of three main currents of Islamic economic thought, namely: First, the Baqir al-Sadr School with its main figures Baqir Sadr and Ali Shariati, this school has an understanding that there are fundamental differences between economics and Islam. Therefore, the term economics must be replaced with the word 'Iqtishad'. This school also tends to disapprove of the conventional economic axiom of 'limited resources, unlimited wants'. Second, the Mainstream Madzhab with its character M.A. Mannan, Umer Chapra, Nejatullah Siddiqi, Monzer Kahf, and Anas Zarqa. If the first is 'fundamentalist' in color, the second is 'middle way' in attitude to conventional economics. Because of its moderate nature, this school is the most dominant, with ideas offered using economic modeling and quantitative methods, and supported by large institutions that support the study and publication of the results of their studies. Third, Alternative Madzhab with its pioneers Timur Kuran and Muhammad Arif. This flow invites Muslims to be critical not only of capitalism and socialism, but also of the currently developing Islamic economy. According to them, Islam must be true, but Islamic economics is not necessarily correct because it is only a human interpretation of Islamic teachings.